Risks at Crypto-Currency Flow at International Financial Markets - Voloshin, Vyacheslav; Belopolsky, Nikolay; Bessonova, Svetlana (International Journal of Engineering and Technology, 2018)
Analyzed in the article are the problems of occupying the financial market and formation of crypto-currencies in todayâ€™s financial world, also analyzed are the aspects of ambiguity in an approach to defining and attitude to crypto-currency in different countries. The objective of the article is discovering advantages and risks of application of crypto-currencies at international financial markets. Analyzed were the factors of influence upon-bitcoin, the most popular crypto-currency. Comparative analysis of the legislation, regulating the flow of crypto-currencies at the financial markets and taxation was performed. Approaches to the essence of crypto-currencies, existing in different countries were studied. Also analyzed were possibilities of passing on to digital money for a number of countries. Conclusions, regarding the risks at passing on to electronic monetary flow for a certain group of countries were arrived at. For Ukraine it was concluded that the country were within the zone of financial risks and the perspective of avoiding payment in cash was out of the question for the immediate future. In the work the advantages and disadvantages of crypto-currency application are listed and various views and hypotheses, regarding the prospects of its existence were considered. The conclusions contain recommendations regarding strengthening the existing standard and legislative base, made with due regard to the experience gained by the developed countries. Â